Food industry perspectives on potential policies targeting unhealthy food and beverage price promotions in Australian supermarkets - Lily Grigsby-Duffy; Adrian J Cameron; Kathryn Backholer; Gary Sacks (BMC, 2022)
Abstract Current supermarket price promotions are likely to encourage unhealthy diets, leading some governments to recently endorse restrictions on price promotions for unhealthy food and beverages. However, little is known about the likely industry response to policy action in this area. The aim of this study was to understand how potential government policies targeting food and beverage price promotions in supermarkets are perceived by food industry stakeholders in Australia. Twelve semi-structured in-depth interviews were conducted with current and former employees of major food manufacturers and food retailers as well as other industry experts with experience related to price promotion practices in the Australian supermarket setting. Data were analysed deductively based on Lewin's organisational change theories and inductively to highlight forces that might drive or restrain change. From an industry perspective, forces likely to create industry opposition to implementation of price promotion policy included: fear of losing competitive advantage; potential financial loss for food retailers and their suppliers; a perception that restrictions on price promotions for unhealthy products will not impact health; and a perception of increased financial cost to consumers. Forces perceived to drive implementation of a policy that would benefit public health included: mandatory regulation; extensive compliance monitoring; support for promoting healthy products; consumer education; and sufficient lead time and support from retailers for implementation. These forces, and the way in which they interact, need to be actively considered as part of efforts to change the healthiness of food and beverage price promotions in supermarkets.